Failure probability and stress distribution of milled porcelain-zirconia crowns with bioinspired/traditional design and graded interface - Ramos, G. F. [UNESP]; Ramos, N. C. [UNESP]; Alves, L. M.M. [UNESP]; Kaizer, M. R.; Borges, A. L.S. [UNESP]; Campos, T. M.B.; Melo, R. M. [UNESP] (Elsevier, 2021)
Objective: To evaluate the failure probability and stress distribution of traditional and bioinspired porcelain-zirconia milled crowns, with and without silica infiltration (graded zirconia). Methods: Traditional crown design had a zirconia infrastructure veneered with porcelain; Bioinspired, had a porcelain infrastructure with translucent-zirconia veneer; Graded and Graded Bioinspired crowns had their zirconia layer infiltrated by silica (n = 25). The cameo surface of each crown (porcelain or zirconia) was glazed. The restoration layers were fused by a vitreous connector and the crowns were adhesively cemented to dies. The specimens were then mechanically cycled in a sliding machine using 100 N load at 4 Hz. The specimens were tested until 2 × 106 cycles, and every 0.5 × 106 cycles the crowns were evaluated under stereomicroscopy for the presence of failures. The stress distribution was inspected with Finite Element Analyses. Results: The predominant failure modes for the Traditional and Graded crowns were delamination and cracking, respectively. The Weibull parameters beta and eta were, respectively: Traditional 1.30 and 2.3 × 106 cycles, and Graded 1.95 and 2.3 × 106 cycles. Thus, the Traditional and Graded crowns presented greater susceptibility to failure due to fatigue, while the Bioinspired and Graded Bioinspired crowns showed no fatigue effect using 100N load, showing beta = 1 and eta of approximately 17 × 106 cycles. Also, through finite element analyses, it was verified that the Bioinspired and Graded Bioinspired crowns presented the best stress distribution on both crowns and dental structures. Significance: Bioinspired and Graded Bioinspired crowns had the lowest failure probability and better stress distribution and may be considered robust long lasting restorations.
Keywords: Ceramic; Glass infiltration; Sol gel; Weibull; Zirconia